Preventive and reparative functions of host-associated probiotics against soybean meal induced growth, immune suppression and gut injury in Japanese seabass (Lateolabraxjaponicus). Issue 128 (September 2022) - Yang, Hong-Ling; Liu, Zi-Yan; Jin, You-Mei; Liu, Zi-Xin; Zhang, Bi-Yun; Yuan, Ze-Hui; Ye, Ji-Dan; Sun, Yun-Zhang
Abstract: A 56-day feeding trial was conducted to examine the preventive and reparative functions of host-associated probiotics against high soybean meal (SM)-induced negative effects in Japanese seabass ( Lateolabrax japonicus ). Fish continuously fed low SM (containing 16% SM) and high SM (containing 40% SM) diets were named as positive (PC) and negative (C) control, respectively. Preventive functions of probiotics were evaluated by continuously feeding diets LF3 ( Lactococcus petauri LF3 supplemented in high SM diet, group PLF3) and LF4 ( Bacillus siamensis LF4 supplemented in high SM diet, group PLF4), while reparative functions were estimated by feeding the high SM diet during 0–28 days, then feeding diets LF3 (group RLF3) and LF4 (group RLF4) until day 56. Compared with the group PC, suppressed growth and immunity, and damaged intestinal health were observed in the group C on days 28 and 56. Fish in groups PLF3 and PLF4, rather than in groups RLF3 and RLF4, showed higher growth compared with the group C and displayed similar immune status to the group PC, indicating that the initial and continued application of probiotic LF3 and LF4 can efficiently improve high SM induced growth and immune deficiency in Japanese seabass, but probiotics had limited reparative benefits when they were administrated at the middle of the feeding trial (28 d). Furthermore, probiotics showed good preventive functions and limited reparative functions on gut health via improving intestinal morphology and inflammation markers, for example, decreasing diamine oxidase activity and d -lactate content, while up-regulating anti-inflammatory TGF-β1 expression and down-regulating pro-inflammatory TNF-α, IL-1β, and IL-8 expressions. Moreover, dietary supplementation of probiotics (especially on day 56) could effectively shape the gut microbiota, such as significantly decreasing abundances of opportunistic pathogens (phylum Actinobacteria, genera Pseudomonas and Moheibacter on day 28, phylum Proteobacteria, genus Plesiomonas on day 56), significantly increasing gut microbial diversity and abundances of possible beneficial bacteria (phylum Bacteroidetes and genus Lactobacillus on day 28, phyla Firmicutes, Bacteroidetes and Cyanobacteria, genera Bacillus, Lactobacillus and Bacteroides on day 56). In conclusion, we evidenced for the first time that host-associated L. petauri LF3 and B. siamensis LF4 can provide effectively preventive and certain reparative functions against high SM-induced adverse effects in L. japonicus . Highlights: Probiotics showed good preventive functions and partly reparative functions in alleviating high SM induced side effects. Host-associated probiotics alleviate SM induced growth and innate immune suppression. Host-associated probiotics shape the intestinal microbiota and relieved inflammation.